Enhancing fouling resistance and separation performance of polyethersulfone membrane through surface grafting with copolymerized thermo-responsive polymer and copper oxide nanoparticles - Homa Ghasemi; Nidal Abu-Zahra; Nadeem Baig; Ismail Abdulazeez; Isam H. Aljundi (Chemical Engineering Journal Advances, 2023)
Surface modification is a critical aspect for improving the efficiency of membranes and reducing the risk of fouling in applications such as wastewater treatment and oil/water separation. The objective of this study is to minimize membrane fouling and maximize its rejection rate through surface modification. Here, for the first time, we developed a dual-functionalized PES membrane using a two-step process, involving grafting with a thermo-responsive polymer (P(NIPAm-co-AAm)) and subsequent functionalization with copper oxide nanoparticles. The membranes were evaluated for any changes in their chemical composition, structural properties, porosity, surface charge, and wetting characteristics. The hydrophilicity of all the modified membranes increased as indicated by a noticeable reduction in the water contact angle. The modified membranes displayed a change in their receding water contact angle based on changes in water temperature, confirming the thermo-responsive nature of PNIPAm. The receding contact angle for the PES membrane grafted with P(NIPAm-co-AAm) was significantly low (∼13°) below 33 °C but increased to 28° when the temperature exceeded 40 °C, indicating the dependence of the surface wettability of the treated PES membranes on temperature. The dual-functionalized membrane outperformed the pristine PES membrane, with a 13% increase in flux and 26% rise in flux recovery ratio. Additionally, the CuO@PES-g-P(NIPAm-co-AAm) membrane showed significant improvements in contaminant rejection and antifouling ability, with > 98% rejection rate for both oil-water emulsion and bovine serum albumin (BSA). The achieved separation and antifouling properties make the dual-functionalized membrane an excellent candidate for water treatment and demonstrate the efficacy of our simple modification process.